IDENTIFIKASI KARAKTER MORFOLOGI DAN ANATOMI TANAMAN JERUK LOKAL (Citrus Sp) DI DESA KARYA AGUNG DAN KARYA ABADI KECAMATAN TAOPA KABUPATEN PARIGI MOUTONG - Murtando, Hefip; Sahiri, Nirwan; Madauna, Ichwan (AGROTEKBIS, 2016)
This study aims to identify the morphology and anatomy characters of local citrus cropat the Karya Agung and Karya Abadi. The collection of materials was done by exploration on the morpholog of local citrus cropsat Karya Agung the Village and Karya Abadi villages located at Taopa district of Parigi Moutong and the anatomy observation was done at Laboratory of Integrated Pest and Diseaseof Agriculture Faculty of Tadulako University. The study was conducted in October to November 2015. Total sample of citrus crop were collected for morphology and anatomy was 20 samples consisting of 10 samples from the Karya Agung and 10 samples Karya Abadi village, respectively and analyzed using cluster analysis and the results will be shown as dendrogram. The results showed in dendogram there ara citrus cultivars diversity in Parigi Moutong, especially in the village Karya Agung and Karya Abadi, it is visible from the morphological characters and specific anatomical features shown by the results of a cluster analysis to look at the level of the great diversity. There are three groups of accessions in Karya Agung village named KA03, KA01 and KA09. Also, three groups ofaccessions in Karya Abadi Village named KB09, KB01 and KB10.Key Words: Anatomy, citrus crop, characters, morphology.